HUKUM DAN KEKUASAAN MENURUT HUKUM POSITIF - Salim, Munir (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
Law for each country is something that is very valuable, so that every citizen to uphold and respect the law above all else. Because the law has an important role in setting the ground rules governing the conduct of government in the life of society, nation and state. The basic rule is the government that must be obeyed by every citizen, in order to create the atmosphere of harmonious, peaceful, just and prosperous as the ideals of a nation. Based despite some basic rules of law that is so neat and systematic adopted a country, but the phenomenon of life of citizens who have needs and desires are different, so it could lead to the behaviors and actions by individuals or groups of people in society who violate the rules applicable laws and regulations. To maintain and preserve the tranquility of living in a society and state, then to the person or group of people who are breaking the law should be prosecuted to the process determine the extent of violations and sanctions will be given by the prosecutor and the judge who has the authority and the power to prosecute and punish the fairly as possible, commensurate with the violation committed deeds.